Resepsi Penggemar Terhadap Karakter Anime Shounen My Hero Academia, Attack on Titan dan Hunter X Hunter - Vinny Anugraha Putri; Wisma Nugraha Ch.R; Suastiwi Suastiwi (ULTIMART Jurnal Komunikasi Visual, 2021)
One of the most important components in a film or animated series apart from the story is the character. The main characters who drive the plot generally are the main focus and also naturally became fans’ favorite character. In several series it is not uncommon to find fans who prefer second lead characters. Why does it happen? There’s not a lot of research regarding the topic of fan receptions to various characters that has been conducted before and it is very interesting and important to be studied. Understanding fans' reception of characters can be understood by means of cognitive narratology approach with ‘categorization and personalization’ theory by Schneider. Murray Smith's ‘structure of sympathy’ theory is also used to further look at the engagement level of fans to their favorite characters. This research is focusing on characters from shounen anime series which have second lead characters that are more popular than the main characters. From this study, identified six categories in fans reception which are personality, character development, goals, design / audio-visual, relationships between characters and emotions. Not only understanding relationships between the characters and emotion, fans also closely following and evaluating the actions that the characters did throughout the story, these factors will also have an effect later on the fans' sense and level of engagement to the characters. Keywords: character; fans reception; engagement; anime